Menerapkan Pendekatan CRT untuk Menumbuhkan Pemahaman Budaya Jawa Peserta Didik - Qona'ah, Annisya'; Nuroso, Harto; Poncowati, Lilik; Purnamasari, Iin (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
This research aims to improve student learning outcomes on Pancasila education content by applying Javanese culture. This research includes quantitative research by taking pretest and posttest data to see whether this research is successful or not. The sample used by researchers was one group consisting of one class totaling 25 students with different characters and emotions. The results of the research show that there is an increase in learning outcomes as evidenced by an increase in learning outcomes from the pretest and posttest. There are 10 students in the high criteria, 9 students in the medium criteria, and 6 students in the low criteria out of a total of 25 students. , while the average posttest score was 87.52 from 25 students. From these gains, there is an average difference of 18.44. With this difference in average, it can be said to be significant because there is an increase in the academic achievement of class IV students at Wonotingal Elementary School.